Mantle cell lymphoma and involvement of lacrimal glands and orbit (Ukrainian Journal of Ophthalmology, 2026)
Mantle cell lymphoma and involvement of lacrimal glands and orbit
Keywords: non-Hodgkin’s lymphoma; mantle cell lymphoma; lacrimal gland; orbit; polychemotherapy